Influence of Glucanoacetobacter Diazotrophicus On The Rootcolonization Of Glomus Fasciculatum And Growth Of Sugarcane - Devika, V (International Journal of Pharmaceutical & Biological Archive, 2014)
Influence of Glucanoacetobacter Diazotrophicus On The Rootcolonization Of Glomus Fasciculatum And Growth Of Sugarcane